Developing a Technology-Integrated Authentic Pragmatic Portfolio Assessment for Mahārah al-Kalām in the Malzamah Akbarnas Program - Fajrotuz Zahroh; R. Umi Baroroh; Triani Agustin; Khaerul Muttakin; Agna Hawari (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2026)
This study aims to develop a technology-integrated portfolio assessment instrument and rubric for mahārah al-Kalām, based on an authentic, pragmatic approach in the Malzamah Program Akbarnas book. Conventional assessment of mahārah al-Kalām tends to focus on structural linguistic aspects and memorization, so it does not fully represent students' Arabic language skills in the context of real communication. The study applied a Research and Development (R&D) design using the Define–Design–Develop (3D) model. Expert validation involved five experts in Arabic language education and educational assessment. The instrument achieved strong content validity (Aiken's V = 0.87) and high internal consistency (Cronbach's Alpha = 0.91), indicating high validity and reliability. A limited trial involving 32 students demonstrated the instrument's practicality and usability in real learning settings. The resulting assessment framework integrates authentic pragmatic tasks, structured rubrics, and digital portfolio documentation to assess speaking competence in contextual and communicative settings. This model offers a replicable framework for Arabic language educators seeking to implement more authentic, systematic, and technology-supported speaking assessments.